DEVELOPMENT AND VALIDATION OF HIGH PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR THE SIMULTANEOUS DETERMINATION OF Β-SITOSTEROL AND LUPEOL IN VERNONIA CINEREA LINN. - WILLY SHAH; M.B.KEKARE; VIKAS VAIDYA (International Journal of Pharma and Bio Sciences, 2010)
A simple, precise and accurate high-performance liquid chromatographic method has been developed for simultaneous determination of β-sitosterol and Lupeol in whole plant powder of Vernonia cinerea Linn. Chromatographic separation of the two compounds was performed on a waters symmetry shield C18 column (150 x 4.6, 5 µm) as stationary phase with a mobile phase comprising of methanol : acetonitrile (30:70) v/v at a flow rate of 1.0 mL min-1 and UV detection at 210nm with a run time of 12.0 min. The proposed method was validated for linearity, accuracy, precision and limit of quantitation. The validated HPLC method can be used for a routine quality control analysis and simultaneous quantitation of β-sitosterol and Lupeol from Vernonia cinerea Linn.